Impacts of Demographic Variables on Creativity Fostering Behaviour Among Undergraduates in Ahmadu Bello University, Federal College of Education, Kontagora Campus - Olawale, Sunday G.; Olaojo, Olubanke A.; Asiyanbi , Mutiat; Ekeh , Augustina Ngozi (International Journal of Educational Management, 2021)
The study investigated impacts of demographic variables on creativity fostering behaviour among undergraduates of Ahmadu Bello University, Kotangora Campus. Creativity fostering behaviour is the major responsibility of classroom teachers being a model to learners. The research design was descriptive expost facto type with a sample of 115, teacher's creativity fostering behaviour scale (TCFBS) by Olawale (2008) was adopted, three null hypotheses were significant data obtained were analysed using descriptive and inferential statistics. Finding revealed that there wassignificant difference in the scores of ABU undergraduate students in teachers creativity fostering behaviour scale (TCFBS) based on gender, while there was no significant in the marital status and teaching experience hence, it was concluded and recommended that teachers and parents are two banks in individual's life just as breathing is essential to survival, therefore stakeholder should promote open communication, mutual respect and creative advice to build and foster creative behaviour of our youths as they are full of energy, ideas, imagination and creativity. Lastly, useful suggestions were preferred.